2009
DOI: 10.1017/s1041610209009387
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity and specificity of the Modified Conflict Tactics Scale for detecting clinically significant elder abuse

Abstract: The MCTS could be used routinely in clinical practice with carers of people with dementia to detect clinically concerning cases of abuse, many of which are currently being missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…(2005)Quality of life instruments used in dementiaZwakhalen, Hamers, and Berger (2007)A behavioural pain scaleAchterberg, Pot, Scherder, and Ribbe (2007)The nottingham health profileGerritsen et al. (2008)The MDS challenging behaviour profileMcCool, Jogerst, Daly, and Xu (2009)Multidisciplinary reportsCooper, Maxmin, Selwood, Blanchard, and Livingston (2009)The Modified Conflict Tactics ScaleBerkhout, Boumans, Mur, and Nijhuis (2009)“7‐S” modelAcierno et al. (2010)The National Elder Mistreatment StudyTriemstra, Winters, Kool, and Wiegers (2010)The consumer quality index long‐term careInspectie voor de Gezondheidszorg, (2010)VrijheidsbeperkingHeidstra‐Wolke (2011)Zelf‐check voor verpleeghuisartsenPillemer et al.…”
Section: Table A1mentioning
confidence: 99%
“…(2005)Quality of life instruments used in dementiaZwakhalen, Hamers, and Berger (2007)A behavioural pain scaleAchterberg, Pot, Scherder, and Ribbe (2007)The nottingham health profileGerritsen et al. (2008)The MDS challenging behaviour profileMcCool, Jogerst, Daly, and Xu (2009)Multidisciplinary reportsCooper, Maxmin, Selwood, Blanchard, and Livingston (2009)The Modified Conflict Tactics ScaleBerkhout, Boumans, Mur, and Nijhuis (2009)“7‐S” modelAcierno et al. (2010)The National Elder Mistreatment StudyTriemstra, Winters, Kool, and Wiegers (2010)The consumer quality index long‐term careInspectie voor de Gezondheidszorg, (2010)VrijheidsbeperkingHeidstra‐Wolke (2011)Zelf‐check voor verpleeghuisartsenPillemer et al.…”
Section: Table A1mentioning
confidence: 99%
“…This scale has been validated for use in family carers of people with dementia. 37 l The Health Status Questionnaire (HSQ) 38 mental health domain measures health-related QoL throughout the age range, is sensitive to change and has been validated in older and younger people. It is summarised as a continuous score, ranging from 0 to 100, with higher scores indicating better outcome.…”
Section: Assessmentsmentioning
confidence: 99%
“…At the lower-bound NICE threshold of £20,000, the START intervention has a 93% likelihood of being seen as cost-effective, rising to 98% at the £30,000 threshold. (20) 23 (26) 41 (24) HADS-D 20 (23) 35 (20) 23 (26) 41 (24) HADS-T 20 (23) 35 (20) 23 (26) 41 (24) MCTS total 32 (37) 59 (34) 40 (46) 78 (45) HSQ mental health 26 (30) 52 (30) 32 (37) 60 (35) QoL-AD total 34 (39) 58 (34) 38 (44) 77 (45) RESULTS NIHR Journals Library www.journalslibrary.nihr.ac.uk…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…The Conflict Tactics Scale (Straus, 2012) is the most widely used tool in family violence research. A modified version of this scale is often used to measure elder abuse in research, although it has been found to not be useful in detecting clinically significant elder abuse (Cooper, Maxmin, Selwood, Blanchard, & Livingston, 2009). The Conflict Tactics Scale conceptualizes aggression, and therefore measures aggression, as direct acts that occur during conflicts.…”
Section: Perpetrated Aggressionmentioning
confidence: 99%